EQUALITY OF THREE SPECIAL M-GONAL NUMBERS - S. Vidhyalakshmi, S. Aarthy Thangam, M.A. Gopalan (International Journal of Advanced Science and Technology, 2020)
Explicit formulas for the ranks of Triangular numbers, Pentagonal numbers, Hexagonal numbers, Heptagonal numbers and Octagonal numbers satisfying the relations , , are obtained.